“ANALISIS PENGARUH KUALITAS JASA UNIVERSITAS BUNDA MULIA TERHADAP LOYALITAS MAHASISWA (STUDI KASUS PADA JURUSAN BIDANG EKONOMI DAN KOMPUTER)” - Destriana Widyaningrum (Journal of Business & Applied Management, 2015)
Loyalty is a form of consumer satisfaction for goods / services received. Satisfaction is formed on the quality of a product that is applied in service. This study aims to analyze the factors that affect student loyalty to quality services Bunda Mulia University, the quality of these services affect the survival of a university to be competitive in the long run. This study is the use of causal effect study, data was taken using a Stratified Random Sampling (STRS) with a sample of 350 students. Data analysis tool used is a structural equation modeling (SEM) in AMOS program 16.SEM analysis results meet the criteria Goodness of Fit Index, which is as follows: the Chi-square = 522.423; Significance probability = 0.000; GFI = 0.867; AGFI = 0.833; CFI = 0.870; TLI = 0.851 dan RMSEA = 0.072. Based on the results of data analysis show that this research model is acceptable and support the research hypothesis, five of the six hypotheses give significant effect and one of hypotheses can’t give effect on loytalty.Key word :Loyalty, Service Quality, Satisfaction, SEM